Impact assessment of strategic goods on government grants and as a result of activity: An analytical study at the General Company of grain trading (Journal of Accounting and Financial Studies ( JAFS ), 2020)
In Iraq,  government contributions to the public companies have become a very important aspect which contributes to the survival and sustainability of these institutions as it consider  one of the main sources of funding, if not it consider the basis of funding.  According to  the vital roles assigned to these institutions to follow up, which usually  include important activities in the national economy, the research focused on studying the field reality of the method used in evaluating the stock of total production and purchases of goods for the purpose of selling the strategic commodities of the General Company for Grain Trade.  As a result, the aim of this study came to came to highlight  on the hypothesis that the existence of correct valuation procedures for the stock of strategic commodities leads to honest and fair data, and to prove the research hypothesis based on the financial statements of the company for the years (2008-2010).     Based on the above, the research came with  conclusions, the most important of which was the absence of a local standard that regulates the accounting transactions of those companies that are based on their continuation on the grants provided to them in general or government support in particular. Accounting prevailing for measuring and evaluating stocks last term in the financial statements in accordance with the accounting standard No. (5) for inventory that does not mean measuring support for stocks last term in the statements of support value achievement, which is a flaw in measuring the amount of support and as a result of the activity.